Mast Cell Mediators: Their Differential Release and the Secretory Pathways Involved - Moon, Tae Chul; Befus, A. Dean; Kulka, Marianna (Frontiers in Immunology, 2014)
Mast cells (MC) are widely distributed throughout the body and are common at mucosal surfaces, a major host-environment interface. MC are functionally and phenotypically heterogeneous depending on the microenvironment in which they mature. Although MC have been classically viewed as effector cells of IgE-mediated allergic diseases, they are also recognized as important in host defense, innate and acquired immunity, homeostatic responses, and immunoregulation. MC activation can induce release of preformed mediators such as histamine from their granules, as well as release of de novo synthesized lipid mediators, cytokines and chemokines that play diverse roles, not only in allergic reactions but also in numerous physiological and pathophysiological responses. Indeed, MC release their mediators in a discriminating and chronological manner, depending upon the stimuli involved and their signaling cascades (e.g., IgE-mediated or Toll Like Receptor-mediated). However, the precise mechanisms underlying differential mediator release in response to these stimuli are poorly known. This review summarizes our knowledge of MC mediators and will focus on what is known about the discriminatory release of these mediators dependent upon diverse stimuli, MC phenotypes and species of origin, as well as on the intracellular synthesis, storage and secretory processes involved.